ANTIOXIDANT ACTIVITY TEST OF BATOK FRUIT EXTRACT (Limonia acidissima) AS AN ADDITIONAL INGREDIENT IN MASK PREPARATIONS - Dwi Putri Rejeki; Ida Mukhlisa; Fitri Humaira (The SDGS Forum Communication, 2026)
Facial masks are a popular skincare product, and natural ingredients are increasingly in demand due to their safety. Batok fruit (Limonia acidissima) is known to be rich in bioactive compounds such as flavonoids and polyphenols, which have the potential as antioxidants to fight free radicals that cause skin damage and premature aging. This study aims to test the antioxidant activity of batok fruit ethanol extract as a basis for developing additional ingredients in mask preparations. This study is an experimental study that begins with the preparation of simplex from batok fruit flesh. Extraction was carried out by maceration method using 96% ethanol solvent for 3x24 hours. The obtained thick extract was then tested for antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method with Vitamin C as a comparator. Determination of antioxidant activity was carried out by measuring the extract's inhibition value against DPPH free radicals using a UV-Vis spectrophotometer to obtain the IC₅₀ value. The results of the characterization of simplex showed that batok fruit powder met the quality standards with a water content of 8.2%. The extraction process of 200 grams of simplicia produced a thick extract of 13.8 grams with a yield of 6.9%. The results of the antioxidant activity test showed that the ethanol extract of batok fruit has a very strong free radical scavenging ability, with an IC₅₀ value of 13.2 ppm. Although this value is not as strong as the comparison of Vitamin C (IC₅₀ 3.57 ppm), these results classify batok fruit extract as a very strong antioxidant (IC₅₀ < 50 ppm). Thus, batok fruit extract has great potential to be developed as a natural active ingredient in facial mask formulations to protect the skin from oxidative damage.